2011
DOI: 10.5664/jcsm.1472
|View full text |Cite
|
Sign up to set email alerts
|

CBT for Insomnia in Patients with High and Low Depressive Symptom Severity: Adherence and Clinical Outcomes

Abstract: Results suggest that pre- to post CBTI improvements in insomnia symptoms, perceived energy, productivity, self-esteem, and other aspects of well-being were similar among patients with and without elevation in depressive symptom severity. Thus, the benefits of CBTI extend beyond insomnia and include improvements in non-sleep outcomes, such as overall well-being and depressive symptom severity, including suicidal ideation, among patients with baseline elevations. Results identify aspects of CBTI that may merit a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
104
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 220 publications
(114 citation statements)
references
References 23 publications
7
104
3
Order By: Relevance
“…Indeed, the majority of empirical studies investigating the insomnia-suicide link and reviews on this topic [15,80] have suggested that CBT-I, the recommended firstline treatment for insomnia [135,136], may be effective for reducing suicide risk. In support of this hypothesis, recent work has found that CBT-I not only impacts insomnia symptoms but also non sleep-related symptoms that are not directly targeted by the therapy [137,138] e including suicide-related ideations [139]. An additional, important consideration is that the components of CBT-I either directly or indirectly target each of the proposed mediators.…”
Section: Insomnia Treatment To Target Potential Mediators?mentioning
confidence: 88%
“…Indeed, the majority of empirical studies investigating the insomnia-suicide link and reviews on this topic [15,80] have suggested that CBT-I, the recommended firstline treatment for insomnia [135,136], may be effective for reducing suicide risk. In support of this hypothesis, recent work has found that CBT-I not only impacts insomnia symptoms but also non sleep-related symptoms that are not directly targeted by the therapy [137,138] e including suicide-related ideations [139]. An additional, important consideration is that the components of CBT-I either directly or indirectly target each of the proposed mediators.…”
Section: Insomnia Treatment To Target Potential Mediators?mentioning
confidence: 88%
“…21 Treating insomnia improves depression and anxiety symptoms, and treating anxiety/depression improves insomnia. [22][23][24] …”
mentioning
confidence: 98%
“…CBT-I has been tested on alcohol-dependent populations and has demonstrated improvements in general sleep quality, 4 sleep efficiency, 59 wake after sleep onset (WASO), 7,8 and general fatigue. 6 The benefits of CBT-I may extend beyond insomnia and include improvements in overall well-being and depressive symptom severity, 10 which may have implications for alcoholics who often suffer comorbid mental disorders and whose lives are otherwise negatively affected by addiction.…”
mentioning
confidence: 99%